Liability of the Head of the Village in the Village financial management according to Law number 6 of 2014 concerning Village - Supriadi, Edy (Jurnal IUS (Kajian Hukum dan Keadilan), 2015)
This research aimed to analyze the regulation of the Village financial management, the mechanism and procedure of the Village financial management and the liability of the head of the Village in the Village financial management according to Law number 6 of 2014 concerning Village. Type of this research is normative legal research, using statutes, conceptual and case approaching method. This research concludes that the head of the Village posses a wide authority as the budget user power which may cause deviation of the Village financial utilization. Hence, the head of the Village requires acknowledgement of the Village Deliberation Body in the financial management supervision yet in the Village financial allocation. Keywords: Liability, Village financial